A friendly rest room : developing toilets of the future for disabled and elderly people - Molenbroek, J. F. M. (Johannes Franciscus Maria), 1951-; Mantas, J. (John); Bruin, Renate de (Assistive technology research series, 2011)
This book addresses the topic of toilet design, but instead of focusing on the typical able bodied user, it takes the various needs and limited abilities of older and/or disabled people as its starting point (human centered design). This follows the principles of 'Inclusive Design': designs taking into account the needs of the most challenged, will also have benefits for the healthy. For the most part, this book is a spin-off of an EU-funded research and development project called the 'Friendly Rest Room for Elderly People' (FFR), which ran from 2001 to 2005. During that period a consortium of.